Reconceptualizing civic education for young children: Recognizing embodied civic action. (March 2020) - Payne, Katherina A.; Adair, Jennifer Keys; Colegrove, Kiyomi Sanchez Suzuki; Lee, Sunmin; Falkner, Anna; McManus, Molly; Sachdeva, Shubhi
Traditional conceptions of civic education for young children in the United States tend to focus on student acquisition of patriotic knowledge, that is, identifying flags and leaders, and practicing basic civic skills like voting as decision-making. The Civic Action and Young Children study sought to look beyond this narrow vision of civic education by observing, documenting, and contextualizing how young children acted on behalf of and with other people in their everyday early childhood settings. In the following paper, we offer examples from three Head Start classrooms to demonstrate multiple ways that young children act civically in everyday ways. When classrooms and teachers afford young children more agency, children's civic capabilities expand, and they are able to act on behalf of and with their community. Rather than teaching children about democracy and citizenship, we argue for an embodied, lived experience for young children.